Nemesis [large type] - Hurwitz, Gregg (Hurwitz, Gregg. Orphan X novel, 2025)
"Evan Smoak was once a highly successful black ops assassin known as Orphan X, dedicated to a rigid set of rules. Tommy Stojack, a gunsmith who created much of Evan's weapons and combat gear, has apparently crossed one of Evan's sharply delineated lines. Now Evan has no choice but to track down and face his only friend. In the meantime, Tommy has already left town to honor an old promise to a Navy friend who died in his arms. While Tommy is trying to keep him and his friends alive, Evan arrives with vengeance in mind. But as deadly as the former Orphan X is, Evan isn't even the most dangerous threat to arrive on the scene"--